The Impact of Environmental Pollution on Human Health: A Review of Pathophysiological Mechanisms and Medical Implications - Ahmed Mohamed Saleh Mahdi; Yasser Muhammad Hamza Jadoua; Alaa Bashir Mohammed Abd (American Journal of Biodiversity, 2025)
Considering the severe impact of environmental pollution on human health, this essay reviews the relevant studies to elucidate the pathophysiological mechanisms and suggests that addressing environmental pollution would bring broad medical and public health implications. The surroundings of individuals and of the environmental condition in which they live have a significant influence on health. Besides the concern of man and the other elements in the environment, there is the consideration of bacteria, viruses, and chemicals, which may adversely affect health. From a health perspective, morbidity and mortality may result from exposure to various pollutants. The environment can also provide therapeutic benefits, including those from natural settings. Environmental problems may contribute to physical, mental, behavioral, and social health problems. Health may be directly influenced by lifestyles, occupations, genetic inheritance, and health care, and it could be indirectly influenced by the environment. A significant contamination in environmental quality requires the dissemination of information, public vigilance and discussion, and activism to recognize its importance in health. Concentrated health threats and pollution, in its different forms and by different paths, could harm health, with implications for the nervous system, endocrine system, reproductive system, cardiovascular system, renal system, immune system, skin, and various other diseases. Since medical studies first investigated the harms and brought health implications into the public sphere, penalties for major contaminations have prevailed. In that sense, public health policies and regulations may address environmental contamination, thereby protecting health by minimizing pollution. Moreover, there is a growing body of evidence revealing the association of substances released into the environment by numerous human activities with major health problems. Based on the data described, it is shown how urgent it is to apply stricter measures to contain the environmental and pollution problem. Thus, this paper elucidates the pathophysiological mechanisms of the impact of environmental pollution on health and suggests broad medical and public health implications.